3D E-Worksheet on Global Warming: Its Impact on High School Students' Critical Thinking Skills - Salsabila Carissma Putri; Eko Hariyono (Universitas Negeri Surabaya, 2026)
Objective: This study aims to describe the implementation of the guided inquiry learning model assisted by a 3D e-worksheet on global warming, analyze improvements in students' critical thinking skills after the learning, and determine students' responses to the learning. Method: The study used a pre-experimental design with a pre-test and post-test group without a control group. The subjects were grade X students of SMA Negeri 1 Kebomas in three classes (experimental class and two replica classes). The research instruments included observation sheets for learning implementation, critical thinking tests (pre-test and post-test) based on Ennis indicators, and student response questionnaires. Data were analyzed using normality and homogeneity tests, paired t-tests, N-Gain, ANOVA, Cohen's effect size, and descriptive analysis of responses. Results: Learning implementation was categorized as very good, with meeting percentages of 86.30%, 89.81%, and 90.74%. There was a significant difference between pre-test and post-test scores (Sig. 0.000). The average N-Gain values in the three classes were 0.443, 0.554, and 0.396 (moderate category), indicating increased critical thinking skills. ANOVA results showed Sig. 0.000, meaning improvement varied across classes. Student responses were good, with average percentages above 70%, reflecting interest and new experiences in technology-based physics learning. Novelty: The novelty lies in integrating 3D e-worksheet, supported by PhET simulations, into a guided inquiry framework on global warming to train students' critical thinking skills, with consistency tested across three classes.